Exome sequencing in 32 patients with anophthalmia/microphthalmia and developmental eye defects. (6th January 2015) - Slavotinek, A.M.; Garcia, S.T.; Chandratillake, G.; Bardakjian, T.; Ullah, E.; Wu, D.; Umeda, K.; Lao, R.; Tang, P.L.‐F.; Wan, E.; Madireddy, L.; Lyalina, S.; et al.
<x xml:space="preserve">Abstract</x> Anophthalmia/microphthalmia (A/M) is a genetically heterogeneous birth defect for which the etiology is unknown in more than 50% of patients. We used exome sequencing with the ACE ExomeTM (Personalis, Inc; 18 cases) and UCSF Genomics Core (21 cases) to sequence 28 patients with A/M and four patients with varied developmental eye defects. In the 28 patients with A/M, we identified de novo mutations in three patients (OTX2, p.(Gln91His), RARB, p.Arg387Cys and GDF6, p.Ala249Glu) and inherited mutations in STRA6 in two patients. In patients with developmental eye defects, a female with cataracts and cardiomyopathy had a de novo COL4A1 mutation, p.(Gly773Arg), expanding the phenotype associated with COL4A1 to include cardiomyopathy. A male with a chorioretinal defect, microcephaly, seizures and sensorineural deafness had two PNPT1 mutations, p.(Ala507Ser) and c.401‐1G>A, and we describe eye defects associated with this gene for the first time. Exome sequencing was efficient for identifying mutations in pathogenic genes for which there is no clinical testing available and for identifying cases that expand phenotypic spectra, such as the PNPT1 and COL4A1‐associated disorders described here.